Efficacy of Tongue Stimulation in Neurorehabilitation– A Narrative Review (Medico Legal Update, 2021)
Introduction: The tongue is being represented bilaterally in the motor homunculus of the brain. Tongue hasbeen used as an effective interface to send signals to central nervous system. The purpose of this article is toreview all articles related to tongue stimulation in neurological rehabilitation.Method: All studies including case studies, cohort studies, experimental studies and reviews, which dealtwith tongue stimulation in neurological conditions during the period between 2010 and 2020, were includedin the study.Results: Tongue Stimulation has been used effectively n rehabilitation for improving balance in patientswith vestibular disorders, multiple sclerosis patients, spinal cord injury patients and stroke patients. TongueStimulation has also been used to improve motor recovery in stroke patients.Conclusion: Tongue stimulation becomes a novel mode of stimulation in inducing neuroplasticity and canbe used in wide variety of neurological patients. Further researches needs to be done on the effect of tonguestimulation on upper extremity rehabilitation in stroke patients.